Factors Influencing The Growth and Development of Children with Stunting, Scoping Review - Novia Dwijayanti; Mufdlilah Mufdlilah (Women, Midwives and Midwifery, 2022)
Background:  Data related to stunting rates known by country include Thailand (10.5%), Sri Lanka (27.3%), Maldives (20.3%), North Korea (27.9%), Myanmar (29.2%). ), Bhutan (33.6%), Nepal (35.8%), Bangladesh (36.1%), Timor Leste (50.2%), India (38.4%), and Indonesia (36.4% ). Referring to the results of the Basic Health Research (Riskesdas) conducted every 5 years, it is known that the percentage of stunting in Indonesia has decreased from 37.2% in 2013 to 30.8% in 2018. Growth and development are closely related to stunting are considered an important indicator of inequality in child health. This can be caused by several factors, both before and after giving birth in the developmental phase, including poor nutrition, household environment, and parents' education and economy. Research Objectives: This study aims to systematically map the research carried out in this field and identify factors that influence stunting growth and development. Methods:  The method used is Prism Flowchart (Preferred Reporting Items For Systematic review and Meta-Analyses). It is used to describe the flow of the literature search. Article searches were conducted using 3 databases (PubMed, Wiley, and ProQuest). The inclusion criteria for articles are articles published in 2015-2020, in English and discuss the Factors Affecting the Growth and Development of Children with Stunting. The article search flow is described using the PRISMA Flowchart, while the article quality assessment is carried out using Hawker and CASP. The next stage is the preparation of data and reporting of results. Result:  Based on the critical appraisal results from 12 articles that have been selected through the cross-sectional method, 11 articles were obtained (A1, A2 A3, A4, A5, A6, A7, A8, A10, A11, A12) and 1 study cohort article (A9). Based on the quality of the articles that have undergone critical appraisal, it was found that several articles obtained grade B (A1, A2, A3, A4, A6, A7, A8, A9, A10, A11, A12) and 1 article received grade D (A5). Conclusion: The findings from this scoping review are that the child's gender, child's age, mother's age, mother's education, mother's occupation, wealth, economy, nutritional status before and after giving birth, clean water sanitation, latrine management, hygiene, and environmental factors, have an effect on stunting which may hinder the growth and development of children in the future.